Fatimid lineage in historical narratives - Asaad, Abdulbari; Ismail, Ferset (Humanities Journal of University of Zakho, 2021)
The Fatimid lineage refers in this paper the lineage of the caliphs of the Fatimid state that were established in the Islamic Maghreb in the year 297H/909AD,and with the hands of Abu Abdullah Al-Shi`i. The case of their lineage has sparked a wide argument between Muslim historians and contemporary researchers. In this research we shed light on their lineage on the part of the confirming and dissenting parties, in addition on the analysis of some contemporary researchers between support and denial. A difference occurred between historians on many topics related to the history of the Fatimid state, starting with the concealed Imam after Muhammad bin Ismail bin Jaafer Al-Sadiq, and the Imams who sent preachers to the Islamic regions, and there is no doubt that this difference influenced the determination of the correct lineage of the (first Fatimid caliph). As well as the policy that he practiced upon receiving the caliphate, and which was justified by many historians by not belonging to the Al albyti.